Pulmonary metastasis from renal epithelioid angiomyolipoma in the setting of breast cancer - MacCraith, Eoin (BMJ Case Rep, 2017)
A 68-year-old woman presented with visible haematuria. Ultrasonography and triphasic CT revealed a 2.6 cm mass in the lower pole of the left kidney. A biopsy suggested low-grade renal cell carcinoma. Radical nephrectomy was performed and revealed an epithelioid angiomyolipoma. At year 3, the patient developed ductal carcinoma of the right breast and underwent a wide local excision and sentinel lymph node biopsy followed by chemotherapy and radiotherapy. 4 months later, she was noted to have a 1.6 cm nodule in the middle lobe of her right lung. The primary differential diagnosis was a breast cancer metastasis. Biopsy revealed a metastatic renal epithelioid angiomyolipoma. The patient elected to have stereotactic radiotherapy over surgical excision. Renal angiomyolipomata are generally regarded as benign tumours. In the present report, we describe the first case of pulmonary metastasis from renal epithelioid angiomyolipoma in the setting of breast cancer.